Cerebrospinal fluid analysis in horses, cattle, and sheep diagnosed with rabies: a retrospective study of 62 cases - Zakia, Luiza S. [UNESP]; Albertino, Lukas G. [UNESP]; Andrade, Danilo G. A. [UNESP]; Amorim, Rogerio M. [UNESP]; Takahira, Regina R. [UNESP]; Oliveira-Filho, Jose P. [UNESP]; Borges, Alexandre S. [UNESP] (Canadian Vet Med Assoc, 2022)
Objectives This study aimed to characterize the findings in cerebral spinal fluid (CSF) analysis of horses, cattle, and sheep diagnosed with rabies. Animals The study included 62 animals (horses, cattle, and sheep) diagnosed with rabies at a referral hospital. Methods This was a retrospective study using medical records from large animals with neurological signs and confirmed positive direct immunofluorescence test for rabies from 2003 to 2020. The results of CSF analysis are presented descriptively. Results Cerebral spinal fluid samples ( N = 67) from 62 animals (31 horses, 24 cattle, and 7 sheep) were retrospectively evaluated. Of these 3 species, 28% (19/67) showed increased protein concentration, whereas 58% (39/67) presented mononuclear pleocytosis. In total, 37% of the samples (25/67) had protein concentration and total nucleated cell count within the reference range. Conclusions and clinical relevance Cerebral spinal fluid from animals diagnosed with rabies was either normal or characterized by mild mononuclear pleocytosis and hyperproteinorrachia.